PHOSPHOLIPIDS FROM PUMPKIN (Cucurbita moschata (Duch.) Poir) SEED KERNEL OIL AND THEIR FATTY ACID COMPOSITION - Tri Joko Raharjo; Laily Nurliana; Sabirin Mastjeh (Universitas Gadjah Mada, 2011)
The phospholipids (PL) of pumpkin (Cucurbita moschata (Duch) Poir) seed kernel and their fatty acid composition were investigated. The crude oil was obtained by maceration with isopropanol followed by steps of extraction yielded polar lipids. The quantitative determination of PLs content of the dried pumpkin seed kernel and their polar lipids were calculated based on the elemental phosphorus (P) contents which was determined by means of spectrophotometric methods. PL classes were separated from polar lipids via column chromatography. The fatty acid composition of individual PL was identified by gas chromatography-mass spectrometry (GC-MS). The total of PL in the pumpkin seed kernels was 1.27% which consisted of phosphatidylcholine (PC), phosphatidylserine (PS) and phosphatidyletanolamine (PE). The predominant fatty acids of PL were oleic and palmitic acid in PC and PE while PS's fatty acid were dominantly consisted of oleic acid and linoleic acid.